A Bivalent Supramolecular GCP Ligand Enables Blocking of the Taspase1/Importin α Interaction. (19th October 2021) - Höing, Alexander; Zimmermann, Alexander; Moews, Lisa; Killa, Matthias; Heimann, Marius; Hensel, Astrid; Voskuhl, Jens; Knauer, Shirley K.
Abstract: Taspase1 is a unique protease not only pivotal for embryonic development but also implicated in leukemia as well as solid tumors. As such, it is a promising target in cancer therapy, although only a limited number of Taspase1 inhibitors lacking general applicability are currently available. Here we present a bivalent guanidiniocarbonyl‐pyrrole (GCP)‐containing supramolecular ligand that is capable of disrupting the essential interaction between Taspase1 and its cognate import receptor Importin α in a concentration‐dependent manner in vitro with an IC50 of 35 μM. Here, size of the bivalent vs the monovalent construct as well as its derivation with an aromatic cbz‐group arose as critical determinants for efficient interference of 2GC . This was also evident when we investigated the effects in different tumor cell lines, resulting in comparable EC50 values (∼40–70 μM). Of note, in higher concentrations, 2GC also interfered with Taspase1's proteolytic activity. We thus believe to set the stage for a novel class of Taspase1 inhibitors targeting a pivotal protein‐protein interaction prerequisite for its cancer‐associated proteolytic function. Abstract : Getting in between : In this communication we present a bivalent supramolecular ligand with guanidiniocarbonyl‐pyrrole (GCP) units able to block the vital interaction between Taspase1 and Importin α. This was also confirmed by determination of the EC50 value in different cell lines.